Solar light induced photocatalytic degradation of tetracycline in the presence of ZnO/NiFe2O4/Co3O4 as a new and highly efficient magnetically separable photocatalyst - Doosti, Mohammadreza; Jahanshahi, Roya; Laleh, Shaghayegh; Sobhani, Sara; Sansano, José Miguel (Frontiers in Chemistry, 2022)
In this study, a new solar light-driven magnetic heterogeneous photocatalyst, denoted as ZnO/NiFe2O4/Co3O4, is successfully prepared. FT-IR, XPS, XRD, VSM, DRS, FESEM, TEM, EDS, and elemental mapping analysis are accomplished for full characterization of this catalyst. ZnO/NiFe2O4/Co3O4, with band gap energy of about 2.65 eV [estimated according to the Tauc plot of (αhν)2 vs. hν], exhibits strong potential towards the efficacious degradation of tetracycline (TC) by natural solar light. It is supposed that the synergistic optical effects between ZnO, NiFe2O4, and Co3O4 species is responsible for the boosted photocatalytic performance of this photocatalyst under the optimal conditions (photocatalyst dosage = 0.02 g·L-1, TC concentration = 30 mg·L-1, pH = 9, and irradiation time = 20 min, and TC degradation efficiency = 98%). The kinetic study of this degradation process is evaluated and it is well-matched with the pseudo-first-order kinetics. Based on the radical quenching tests, it can be perceived that •O2− species and holes are the major contributors in such a process, whereas the •OH radicals identify to have no major participation. The application of this methodology is implemented in a facile and low-cost photocatalytic approach to easily degrade TC by using a very low amount of the photocatalyst under natural sunlight source in an air atmosphere. The convenient magnetic isolation and reuse of the photocatalyst are surveyed too, which further highlights the operational application of the current method. Notably, this method has the preferred performance among the very few methods reported for the photocatalytic degradation of TC under natural sunlight. It is assumed that the achievements of this photocatalytic method have opened an avenue for sustainable environmental remediation of a broad range of contaminants.